2013
DOI: 10.1089/lrb.2013.0023
|View full text |Cite
|
Sign up to set email alerts
|

An Immunological Fingerprint Differentiates Muscular Lymphatics from Arteries and Veins

Abstract: The principal function of the lymphatic system is to transport lymph from the interstitium to the nodes and then from the nodes to the blood. In doing so lymphatics play important roles in fluid homeostasis, macromolecular/antigen transport and immune cell trafficking. To better understand the genes that contribute to their unique physiology, we compared the transcriptional profile of muscular lymphatics (prenodal mesenteric microlymphatics and large, postnodal thoracic duct) to axillary and mesenteric arterie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 62 publications
3
17
0
Order By: Relevance
“…Currently, we are trying to determine what the triggers early recruitment of immune cells to the tissue surrounding the lymphatic vessels since we believe this is a critical early factor that could modulate lymph flow. However, based on the literature we speculate that it is likely some form of innate immune cells that reside near the vessel releasing chemoattractive substances (22). Additionally we would also like to address if this paradigm is common to other chronic inflammatory states, that is whether or not the reduction of lymph flows from different tissues is a common triggering factor in human inflammatory diseases and if preserving lymphatic flow may attenuate inflammation in those diseases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, we are trying to determine what the triggers early recruitment of immune cells to the tissue surrounding the lymphatic vessels since we believe this is a critical early factor that could modulate lymph flow. However, based on the literature we speculate that it is likely some form of innate immune cells that reside near the vessel releasing chemoattractive substances (22). Additionally we would also like to address if this paradigm is common to other chronic inflammatory states, that is whether or not the reduction of lymph flows from different tissues is a common triggering factor in human inflammatory diseases and if preserving lymphatic flow may attenuate inflammation in those diseases.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the primary function of the lymphatic system is to serve and support the adaptive immune system. Indeed anatomically the body’s network of lymphatic vessels is centered on the lymph nodes, with the afferent lymphatic network delivering immune elements from the interstitium to the node and the efferent lymphatic network transporting immune elements from the node to the blood for eventual distribution throughout the body (15, 22–26). CSF1R and PU.1 knockout mice show that interruptions of monocyte development and differentiation leads to the formation of a dysplastic lymphatic network, supporting this principle since the monocyte lineage is responsible for regulating innate and adaptive immunity (27, 28).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(19)(20)(21). LECs both attract and facilitate transmigration of immune cells through a number of signaling axes, many of which have been identified in LEC gene expression studies (22)(23)(24)(25)(26). In addition to identifying multiple cytokines and receptors expressed by LECs under steady-state conditions (22), these studies also identified genes that are upregulated during localized inflammatory processes such as in models of contact hypersensitivity (23), tumor drainage (25), and inflammation (26).…”
Section: Figurementioning
confidence: 99%
“…The collecting lymphatics are distinguished by having both endothelial and smooth muscle layers, and an adventitia that can contain fibroblasts, connective tissue, MHC-II+ antigen presenting cells, nerves that innervate the vessel, and vasa vasorum (Bridenbaugh et al, 2013; Schmid-Schonbein, 1990; Zawieja et al, 2008). While the lymphatic smooth muscle cell organization varies between species, in general the amount of smooth muscle increases when moving centrally along the lymphatic tree.…”
Section: Organization Of the Lymphatic Systemmentioning
confidence: 99%